The Role of Shariah Compliance in Moderating the Relationship between Intellectual Capital and Sustainable Financial Performance - Azwansyah Habibie; Saparuddin Siregar; Kamila Kamila; Andri Soemitra; Nurlaila Nurlaila (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
This study examines the influence of accounting and marketing digitalization on the financial performance of digital banks in Indonesia, a sector that has grown rapidly in response to technological advancements. Although technologies such as eXtensible Business Reporting Language (XBRL) and Customer Relationship Management (CRM) have been widely adopted, their individual impacts on financial performance remain unclear. This research aims to determine the effects of XBRL and CRM, both individually and simultaneously, on Return on Assets (ROA) as a measure of financial performance. Using a quantitative approach, the study employs multiple linear regression analysis based on secondary data collected from the annual reports of 32 digital banks registered in Indonesia. The findings show that XBRL does not significantly affect ROA, as indicated by low correlation and regression coefficients with significance values above 0.05. Moreover, CRM does not have a significant impact when assessed partially, although strong correlations with ROA are observed. However, when analyzed together, XBRL and CRM show a significant simultaneous effect on ROA, explaining 61.5% of the variance. This suggests that while these technologies may not be impactful on their own, their integration can substantially enhance financial performance. Limitations of this study include reliance on secondary data and a narrow focus on ROA, which may not fully capture all dimensions of performance. The findings offer valuable insights for digital banking stakeholders aiming to enhance financial outcomes through comprehensive digital strategies